The proteome profile of embryogenic cell suspensions of Coffea arabica L. - Campos, N.; Paiva, L.; Panis, Bartholomeus; Carpentier, Sebastien C. (Wiley, 2016)
Somatic embryogenesis, is a process by which new viable embryos are produced from somatic tissues. Somatic embryogenesis is not only a useful biotechnological tool for the massive clonal propagation and genetic engineering but it also allows to obtain fundamental knowledge about the molecular changes that take place during embryogenesis. We present the proteome profile of two embryogenic cell suspensions. We identified 1052 non‐redundant proteins. We present their known GO annotations and show two protein networks sharing the GO annotations related to stress and embryogenic capacity via the free program Cytoscape. To our knowledge these results give the first high‐throughput proteome description of embryogenic cell suspensions and provide new information about somatic embryos for the whole plant community. The published proteome is a first step toward understanding somatic embryogenesis in coffee and toward a better annotation of proteins in an important non‐model crop. All data are available via ProteomeXchange with identifier PXD002963.